Pengelolaan dan Kuantisasi Umpan Balik Terbuka dalam Evaluasi Kepuasan Pengguna Aplikasi Darisini - Aisyah Nurul Afyna; Astie Darmayantie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Darisini is a digital platform based on Islamic values that provides various da’wa activities, communities, and collaborative initiatives for social good. Evaluating user satisfaction is essential to ensure that the application meets user needs. This study aims to analyze the level of user satisfaction with the Darisini application and to quantify open-ended feedback in order to identify aspects that require improvement. This research adopts a mixed-method approach with a convergent design. Quantitative data were collected through a structured questionnaire based on the Technology Acceptance Model (TAM) and End User Computing Satisfaction (EUCS). Meanwhile, qualitative data were obtained from open-ended feedback provided by respondents, particularly for indicators with low satisfaction scores. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through text preprocessing, aspect grouping, sentiment identification, and frequency quantification of feedback for each aspect. The results indicate that overall user satisfaction with the Darisini application falls within the very satisfied category. However, the quantification of open-ended feedback reveals several aspects that still require improvement, particularly in terms of usability and content relevance. These findings are expected to serve as a basis for feedback management and future development of the Darisini application.